Zwangsbehandlung bei Selbstgefährdung 14. Göttinger Workshop zum Familienrecht 2015 - Coester-Waltjen, Dagmar; Lipp, Volker; Schumann, Eva; Veit, Barbara (Universitätsverlag Göttingen, 2016)
This book presents the lectures of the 14th Göttingen Workshop on Family Law, which took place on 13th November 2015 and was organized in cooperation with the Center for Medical Law of the University of Göttingen. It deals with the highly relevant problem of coercive medical treatment of a patient who rejects medical treatment and thereby endangers himself. The lectures published in this book analyze the problem for adult patients and for children and young patients from a legal perspective (Georg Dodegge, Isabell Götz), from the point of view of psychiatry (Andreas Heinz, Sabine Müller and Marc Allroggen, Jörg M. Fegert), of medical ethics (Alfred Simon), and from the perspective of human rights (Stefanie Schmahl).